Association between duration of excessive weight and arterial stiffness in middle-aged and older adults. (2nd April 2020) - Matsui, Masahiro; Yoshikawa, Toru; Mizushima, Ryoko; Tanahashi, Koichiro; Myoenzono, Kanae; Tanaka, Kiyoji; Maeda, Seiji
ABSTRACT: This study aims to evaluate the association between duration of overweight/obesity and arterial stiffness. In total, 103 men and women aged 45–68 years with a body mass index (BMI) of ≥25 kg/m 2 were enrolled in this study. Duration of overweight/obesity was calculated for individuals with at least two consecutive BMI occurrences of ≥25 kg/m 2 in the previous (5-year intervals from 20 years old) and present BMI information. Multiple regression analysis showed that carotid-femoral pulse wave velocity, an index of arterial stiffness, was independently associated with the duration of overweight/obesity, but not with current degree of overweight/obesity.